Legal regulation of veterinary safety in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article, in order to ensure the country’s food and raw materials provided by the package of measures for the development of agriculture. Special facilities, with the development of farming, livestock products joldarıqarastırılğan to increase in the future. At the same time, livestock and processing of raw materials discussed the mechanisms of legal regulation. Livestock identification and treatment of diseases of the leading methods and find ways and implementation, as well as diseases of animals and birds, as well as the implementation of cost-cutting measures in the veterinary and sanitary examined regulation of the legal system at a high level.Key words: animal husbandry, veterinary medicine, veterinary safety, food security.The article, in order to ensure the country’s food and raw materials provided by the package of measures for the development of agriculture. Special facilities, with the development of farming, livestock products joldarıqarastırılğan to increase in the future. At the same time, livestock and processing of raw materials discussed the mechanisms of legal regulation. Livestock identification and treatment of diseases of the leading methods and find ways and implementation, as well as diseases of animals and birds, as well as the implementation of cost-cutting measures in the veterinary and sanitary examined regulation of the legal system at a high level.Key words: animal husbandry, veterinary medicine, veterinary safety, food security.